APRESIASI MASYARAKAT DALAM PERTUNJUKAN ORGAN TUNGGAL DI KENAGARIAN ANDING KABUPATEN LIMA PULUH KOTA - Akhyar Ulfa; Marzam Marzam; Wimbrayardi Wimbrayardi (FBS Universitas Negeri Padang, 2013)
Abstract The research described how the society of Anding appreciated the performance of organ tunggal rather than tradisional arts in order to celebrate their wedding. To consider the phenomenon more, the research was based on the appreciation theory given by Aminudin 2000:34, that appreciate was derived from latin word apreciatio which means appreciating. After observation and interview done to several informants it was concluded that people liked to have organ tunggal better in their wedding celebration due to 1) the difference in the payment, tradisional art compared to organ tunggal 2) the dance of the singers (female singers) 3) economic aspect. Kata kunci: Apresiasi, masyarakat Anding, Organ Tunggal, Pesta Pernikahan Abstract The research described how the society of Anding appreciated the performance of organ tunggal rather than tradisional arts in order to celebrate their wedding. To consider the phenomenon more, the research was based on the appreciation theory given by Aminudin 2000:34, that appreciate was derived from latin word apreciatio which means appreciating. After observation and interview done to several informants it was concluded that people liked to have organ tunggal better in their wedding celebration due to 1) the difference in the payment, tradisional art compared to organ tunggal 2) the dance of the singers (female singers) 3) economic aspect. Kata kunci: Apresiasi, masyarakat Anding, Organ Tunggal, Pesta Pernikahan